Analisa Pengaruh Kecepatan Spindel dan Kedalaman Pemakanan Terhadap Kekasaran Permukaan Pada Proses Frais Muka dengan Material Baja ST 37 - Ahmad Raudy; Reny Afriany; Arie Yudha Budiman (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This research aims to examine the effect of spindle speed and feed depth on surface roughness in the edge milling process with ST 37 steel material. A smooth surface is one of the main indicators in assessing the quality of machining results because it directly influences wear resistance, processing and performance of machine components. The independent variables in this study include spindle speed (360 rpm, 580 rpm and 875 rpm) as well as feeding speed (40 mm/min) and feeding depth Fz while the limiting variable is surface roughness (Ra). The machining process was carried out using a vertical milling machine with an HSS endmill chisel with a diameter of 10 mm. Roughness measurements were carried out using a Surface Roughness Tester type SJ-310. The test results show that increasing spindle speed tends to reduce the surface roughness value, which indicates a smoother surface quality. Conversely, a high feed rate causes an increase in roughness. The combination of the highest spindle speed (875 rpm) with the lowest feed speed (40 mm/min) provides the smoothest surface results. These findings confirm that the selection of appropriate machining parameters greatly influences the final quality of the milled surface.